Penerapan Media Pembelajaran Berbasis Gamifikasi untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran IPAS Kelas V MI NU Metro - Lutviana, Ani; Amrulloh, Hanif; Laili, Nur (Universitas Nusantara PGRI Kediri, 2025)
This study aims to implement gamification-based learning media as a strategy to increase learning motivation of class V.a students of MI NU Metro. Gamification that includes the implementation of game components that include points, levels, badges, and leaderboards can offer a fun and challenging learning experience for students. By using an experimental research style, this study uses quantitative techniques. This type of research randomly places participants into one of two groups: a control group and an experimental group. We study and identify the problems faced in implementing gamification media and its usefulness in increasing student learning motivation. Based on the results of this study, gamification media can increase students' enthusiasm for learning. Interactive media in the form of quiz games from (canva) is the most successful and significant gamification learning media in increasing learning motivation. Several challenges in its implementation, identified such as differences in technology access and the need for curriculum adaptation, this article recommends solutions such as teacher training and student involvement in gamification media. With the right strategy, gamification media has the potential to create a dynamic and student-centered learning atmosphere, thereby helping them achieve their maximum potential in education.